2019
DOI: 10.1111/1759-7714.13142
|View full text |Cite
|
Sign up to set email alerts
|

HOXB7 mediates cisplatin resistance in esophageal squamous cell carcinoma through involvement of DNA damage repair

Abstract: Background DNA damage repair is an important mechanism of platinum resistance. HOXB7 is one member of HOX family genes, which are essential developmental regulators and frequently dysregulated in cancer. Recently, its relevance in chemotherapy resistance and DNA damage repair has also been addressed. However, little is known regarding the association between HOXB7 and chemotherapy resistance in esophageal squamous cell carcinoma (ESCC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…GEO data were obtained from the GEO database. The results of CNC analysis demonstrated that 69 mRNAs were co-expressed with LINC00491, including the oncogenes thyroid hormone receptor interactor 13 (TRIP13) ( 24 ) and homeobox B7 (HOXB7) ( 25 ), which are associated with ESCC ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…GEO data were obtained from the GEO database. The results of CNC analysis demonstrated that 69 mRNAs were co-expressed with LINC00491, including the oncogenes thyroid hormone receptor interactor 13 (TRIP13) ( 24 ) and homeobox B7 (HOXB7) ( 25 ), which are associated with ESCC ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that HOXB7 dysregulation may play an important role in a variety of diseases including cancer. It is aberrantly expressed in a variety of cancers, including melanoma ( Carè et al, 2001 ), colorectal cancer ( Kanai et al, 2010 ), hepatocellular carcinoma ( Huan et al, 2017 ), breast cancer ( Heideman et al, 2015 ), esophageal squamous cell carcinoma ( Zhou et al, 2020 ), intrahepatic cholangiocarcinoma ( Dai et al, 2019 ), gastric cancer ( He et al, 2017 ), pancreatic cancer ( Chile et al, 2013 ), and other tumors. However, there are few reports on the relationship between HOXB7 and gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Homeobox B7 (HOXB7), a member of the homeobox family abnormally overexpressed in a variety of solid tumors, plays an important role in proliferation, migration and invasion of tumor cells ( Carè et al, 2001 ; Kanai et al, 2010 ; Chile et al, 2013 ; Heideman et al, 2015 ; He et al, 2017 ; Huan et al, 2017 ; Dai et al, 2019 ; Zhou et al, 2020 ). Its expression is closely related to clinicopathological features, but the signaling pathways causing this phenotype have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells' sensitivity to this peptide is highly correlated to their HOX expression profile, albeit the subset of HOX genes which act as oncosuppressors is not affected [34]. This peptide has shown to be effective in oesophageal and oral squamous cell carcinomas [36,37], melanoma [35,38], ovarian cancer (OC) [39], breast cancer [40], meningioma [41], prostate cancer [42], and leukaemia [43]. The use of RNA interference mechanisms [44,45] and the control of HOX methylation status [46] are additional tools that can control HOX expression with therapeutic function.…”
Section: Hox Genes and Cancermentioning
confidence: 99%